Penerapan Metode Quiz Team Pada Mata Pelajaran Ilmu Pengetahuan Sosial Materi Sumpah Pemuda Untuk Meningkatkan Prestasi Belajar Siswa Kelas VG Madrasah Ibtidaiyah Negeri Malang 1 - Rohmawati, Aulia (Jurnal al Hikmah, 2017)
Ilmu Pengetahuan Sosial is a subject that examines a set of events, facts, concepts and generalizations related to social issues. Through Ilmu Pengetahuan Sosial subjects, students are directed to become democratic, responsible Indonesian citizens, as well as citizens of a peace-loving world. The objectives of Ilmu Pengetahuan Sosial are to have a commitment and awareness of social values and humanity and have the ability to communicate, work together and compete in a pluralistic society, local, national, and global.Quiz team method as one of the alternative methods that make lessons more effective and active and fun, which is expected to increase beberaa points in order to improve student learning achievement on the subject matter of Social Science Sumpah Pemuda. To improve some points in order to improve student achievement, the author in his research through the implementation of quiz team method to improve student achievement of class VG MIN Malang 1 on Sumpah Pemuda material.Moving from the problems above, then the formulation of the problem in this study is How the implementation of quiz team methods to improve student achievement class VG MIN Malang 1. While the purpose of this study is to describe the application of quiz team methods to improve student achievement class VG MIN Malang 1.This study uses a classroom action research design with independent research type. Technique of data collection is done by using observation, documentation, and rating scale. Qualitative data were analyzed by qualitative descriptive analysis while quantitative data were analyzed by quantitative descriptive analysis.The result of analysis shows that the application of quiz team method can improve students learning achievement on IPS subject matter Sumpah Pemuda class VG MIN Malang. 1. It is proven from data of cycle I, student test result is 70% with average value 78,3. In the second cycle, the students test result is 83.3% with an average score of 83. This research proved to give improvement, improvement and change of 83%